2004
DOI: 10.1038/sj.bjc.6601441
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition, lifestyle and colorectal cancer incidence: a prospective investigation of 10 998 vegetarians and non-vegetarians in the United Kingdom

Abstract: In a cohort of 10 998 men and women, 95 incident cases of colorectal cancer were recorded after 17 years. Risk increased in association with smoking, alcohol, and white bread consumption, and decreased with frequent consumption of fruit. The relative risk in vegetarians compared with nonvegetarians was 0.85 (95% CI: 0.55 -1.32).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
95
0
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 11 publications
6
95
0
3
Order By: Relevance
“…vegetarians (Sanjoaquin et al, 2004;Key et al, 2009). We also noted previously in EPIC-Oxford, that the incidence of colorectal cancer among vegetarians was identical to that in the general population of England and Wales (standardised incidence ratio 102% (95% CI: 80 -129); Key et al, 2009).…”
Section: Cancer Incidence In British Vegetarians Tj Key Et Almentioning
confidence: 64%
See 2 more Smart Citations
“…vegetarians (Sanjoaquin et al, 2004;Key et al, 2009). We also noted previously in EPIC-Oxford, that the incidence of colorectal cancer among vegetarians was identical to that in the general population of England and Wales (standardised incidence ratio 102% (95% CI: 80 -129); Key et al, 2009).…”
Section: Cancer Incidence In British Vegetarians Tj Key Et Almentioning
confidence: 64%
“…In the Adventist Health Study in California, vegetarians had a significantly lower risk for cancers of the colon and prostate than non-vegetarians, but the risk for breast cancer did not differ significantly between these dietary groups (Fraser, 1999). In Britain, the Oxford Vegetarian Study suggested no large difference in the incidence of colorectal cancer between vegetarians and non-vegetarians (Sanjoaquin et al, 2004), whereas the UK Women's Cohort Study suggested that women who did not eat any meat had a lower risk for breast cancer than did meat eaters (Taylor et al, 2007). The first results from EPIC-Oxford suggested that the incidence of breast cancer did not differ significantly between vegetarians and non-vegetarians (Travis et al, 2008), that the incidence of colorectal cancer was higher in vegetarians than in meat eaters, that the incidence of lung cancer was lower in fish eaters than in meat eaters, and that the risk for all malignant cancers was lower in fish eaters and possibly lower in vegetarians than in meat eaters (Key et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on fermented milk products such as yoghurt suggest no relationship with CRC risk (22,23,30,38) . For cheese intake, RR range from 0·68 to 1·35 and in most studies the RR was greater than 1·0, although none of these relationships were statistically significant (17,22,23,27,30,34,38) . Some studies (27,38) have attempted to separate hard cheese from soft cheeses such as ricotta and cottage cheese, with the latter appearing to have a protective effect; however, the relationships were not significant and it is difficult to draw any reasonable conclusions from such few studies.…”
Section: Epidemiological Studies Of Dairy Products and Colorectal Canmentioning
confidence: 99%
“…Milk is the dairy product that shows the most consistent relationship with CRC risk. Of the cohort studies to date that have investigated this relationship, most showed nonsignificant decreased risks of CRC with increasing milk intake (12,17,19,22,23,27,29,30,33,34,38) . Most studies have considered all types of milk together, but where these have been separated there are differences between low-fat v. whole milk.…”
Section: Epidemiological Studies Of Dairy Products and Colorectal Canmentioning
confidence: 99%